Cover crop and phosphorus fertilizer management implications for water quality in a no-till corn-soybean rotation - Carver, Robert Elliott (Kansas State University, 2022)
Phosphorus (P) is an essential nutrient required for crop growth with finite global reserves. Although naturally occurring concentrations of total P in soils may greatly exceed crop demand, quantities of readily plant-available P in soil solution are typically very low. As such, agricultural producers regularly apply P-containing fertilizers to help optimize crop yields. While applications of P fertilizers may improve crop performance, losses of P from non-point agricultural sources are a known contributor to the degradation of surface water quality with excessive P inputs leading to eutrophication, harmful algal blooms, and increased water treatment costs. Acknowledging the importance of P in production agriculture and the role it plays in water quality it is imperative to develop agricultural management systems designed to promote crop yields while protecting water quality. This study explores the interplay between winter grown cover crops and P fertilizer management practice in relation to annual concentrations and loads of total suspended solids, total P, and dissolved reactive P in surface runoff generated by natural precipitation events for a no-till corn (Zea mays)-soybean (Glycine max) rotation located in the Central Great Plains. To explain the mechanisms behind the potential implications of altering cover crop and/or P fertilizer management practice in relation to water quality, this study examined temporal/seasonal variability in surface runoff water quality, changes in soil fertility status, and the impact of winter cereal cover crop species on potential P release and nutrient cycling. The majority of this research was conducted at the Kansas Agricultural Watershed (KAW) field laboratory located near Manhattan, KS, USA, from September 2015 through September 2019. This study utilized three methods of P fertilizer management (no P, fall broadcast P, and spring injected P) each expressed with and without a winter grown cover crop. The spring injected method of P fertilizer application consistently lost less total P and DRP compared to the fall broadcast method of applying P fertilizer highlighting the importance of using P fertilizer placement to protect water quality. Findings from this study show that the addition of a cover crop during a normally fallow period increased dissolved reactive P loss in 3 of 4 years representing an unintended consequence of a traditionally recognized conservation practice. Cover crops also decreased sediment loss with greater reductions in sediment loss coming from the P fertilized cover crop treatments. Soil test data for samples collected from KAW field lab found that spring subsurface placement of P fertilizer did not result in lesser concentrations of either Mehlich-III not total P in the top 0-5 cm compared to fall broadcast P. The spring injected P fertilizer without a cover crop treatment had lesser concentrations of water-extractable P (WEP) in the top 0-2.5 cm compared to the fall broadcast with and without cover crop treatments; however, when a cover crop was added to the spring injected treatment, WEP was found to be equal to the two fall broadcast treatments The final portion of this research was conducted from fall 2019 through fall 2021 at locations near both Manhattan, KS, USA and Leonardville, KS, US, and examined the impact of six choices in winter cereal cover crops [included winter barley (Hordeum vulgare), winter oat (Avena sterilis), cereal rye (Secale cereale), triticale (X Tritico-secale), winter wheat (Triticum aestivum), and Cereal Killer Blend (1:1:1:1 of barley:oat:rye:triticale)] on P release from cover crop tissue, residue persistence, and the effect of cover crop choice on nutrient cycling throughout the cash crop growing season. This study found winter wheat to have the greatest potential for P release immediately following termination; however, after one week post termination, P concentrations in winter wheat residues were similar to other observed cover crops. Oats were observed to have lowest residue persistence and also to release assimilated nutrients faster than the remaining species. Marginal differences between winter barley, cereal rye, and triticale were observed with regards to P concentration, residue persistence, and nutrient cycling; however, these differences were not biologically significant. Results from this and the aforementioned studies highlight the importance and implications of management decisions when developing agricultural management practices to protect surface water quality.
Keywords: Cover crop; Phosphorus; Water quality; Surface runoff